Analysis of Sustainability Practices: Case Study on Indonesian Financial Intelligence Units - Purwaningsih, Eti; Siregar, Sylvia Veronica Nalurita Purnama (Yayasan Riset dan Pengembangan Intelektual, 2025)
Sustainability has become a critical global issue as awareness of the social, economic, and environmental impacts of human activities increases. The Sustainable Development Goals (SDGs) provide a universal framework guiding institutions, including Financial Intelligence Units (FIUs), to foster inclusive and sustainable development. FIU Indonesia plays a strategic role in this effort by promoting financial stability, combating money laundering (AML), and countering the financing of terrorism (CFT). This study evaluates the alignment of FIU Indonesia's Strategic Plan (Renstra) 2020-2024 with the SDGs and the National Medium-Term Development Plan (RPJMN) 2020-2024, assesses its program contributions to the SDGs, and designs a sustainability roadmap for the agency. A qualitative case study approach was employed, involving semi-structured interviews with 10 stakeholders from relevant internal units within FIU Indonesia, along with document analysis. The findings show that FIU Indonesia's 2020-2024 Strategic Plan is aligned with the RPJMN policy direction, particularly in supporting political, legal, and security stability. However, FIU Indonesia's contribution to the RPJMN is indirect due to its role as a supporting agency. Furthermore, while FIU Indonesia's strategic plan addresses sustainability aspects, a direct link between the organization's strategy and the SDGs has not been explicitly seen. The Renstra's focus is more on achieving the institution's internal vision and mission. FIU Indonesia has significantly supported the SDGs through inclusive training (SDGs 4.5), labor protection (SDGs 8.8), global governance (SDGs 10.6, 16.8), increased state revenue (SDGs 17.1), and information transparency (SDGs 16.10). However, gaps remain in resource efficiency (SDG 6), gender equality (SDGs 5.1, 5.5), and environmental crime detection (SDG 15). Enhanced focus is also required on combating human trafficking (SDG 8.7), child exploitation (SDG 16.2), and marine ecosystem preservation (SDG 14). The study recommends integrating the AML and CFT program into the RPJMN 2025-2029 as a priority with measurable indicators. Strengthened cross-sector collaboration, adoption of big data and AI for detecting suspicious transactions, and strategic regulations such as the Asset Forfeiture Law are crucial. Public education and media engagement are also essential for broader societal participation. These actions aim to fortify FIU Indonesia's contributions to national and global sustainable development goals.